Biased by Choice: How Financial Constraints Can Reduce Financial Mistakes - Heimer, Rawley Z; Imas, Alex (Review of Financial Studies, 2022)
Abstract We show that constraints can improve financial decision-making by disciplining behavioral biases. In financial markets, restrictions on leverage limit traders’ ability to borrow to open new positions. We demonstrate that regulation that restricts the provision of leverage to retail traders improves trading performance. By increasing the opportunity cost of postponing the realization of losses, leverage constraints improve traders’ market timing and reduce their disposition effect. We replicate these findings in two distinct experimental settings, further isolating the mechanism and demonstrating generality of the results. The interaction between constraints and behavioral biases has implications for policy and choice architecture.